2010
DOI: 10.1002/acp.1736
|View full text |Cite
|
Sign up to set email alerts
|

Alien psychology: Associations between extraterrestrial beliefs and paranormal ideation, superstitious beliefs, schizotypy, and the Big Five personality factors

Abstract: This study examined the associations between the belief that intelligent extraterrestrial life has visited Earth and that governmental agencies have knowledge of this fact and various individual psychological difference factors. A total of 433 participants completed measures of extraterrestrial beliefs, paranormal beliefs, superstitious ideation, schizotypy, the Big Five personality factors, and demographic variables. Results showed that extraterrestrial beliefs were significantly predicted by paranormal belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
2
16
1
3
Order By: Relevance
“…In addition, Newby and Davis (2004) found a link between Locus of Control and New Age paranormal beliefs (reincarnation, astrology, precognition, and witchcraft) with people exhibiting higher views of external control having higher beliefs in these subjects. Similarly, people who report being abducted by aliens score high on tests of fantasy proneness, psychological absorption and childhood imaginings, and introversion (Parnell 1988;Parnell and Sprinkle 1990;Swami et al 2011). Sharps et al (2010) also found that increased paranormal belief was associated with increased dissociative thinking (lower analytical or fact-based thinking processes and higher intuitive or gestalt thinking).…”
Section: Student's Propensity For Beliefmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Newby and Davis (2004) found a link between Locus of Control and New Age paranormal beliefs (reincarnation, astrology, precognition, and witchcraft) with people exhibiting higher views of external control having higher beliefs in these subjects. Similarly, people who report being abducted by aliens score high on tests of fantasy proneness, psychological absorption and childhood imaginings, and introversion (Parnell 1988;Parnell and Sprinkle 1990;Swami et al 2011). Sharps et al (2010) also found that increased paranormal belief was associated with increased dissociative thinking (lower analytical or fact-based thinking processes and higher intuitive or gestalt thinking).…”
Section: Student's Propensity For Beliefmentioning
confidence: 99%
“…Several psychological measures are correlated with increased belief in the paranormal (Hergovich et al 2008;Swami et al 2011), including views of external control (Newby and Davis 2004), magical ideation and referential thinking (Eckblad and Chapman 1983;Lenzenweger et al 1997), and introversion (i.e., absorption; Tellegen and Atkinson 1974;Lobato et al 2014). This study also found an association between these psychological measurements and students' pre-course paranormal and pseudoscientific beliefs.…”
Section: Student's Propensity For Beliefmentioning
confidence: 99%
See 1 more Smart Citation
“…This association could be explained by certain personality traits, such as neuroticism. Cognitive disorganisation, which includes social anxiety, is associated with neuroticism (a preoccupation with negative affect) more than any other personality trait from the five-factor model (Swamih et al, 2011). Schizotypal traits denoting social avoidance, that is negative schizotypy, are associated with lower extraversion and agreeableness (Kwapil et al, 2008;Swamih et al 2011).…”
Section: Social Quality Of Life (Qol) Could Explain the Relation Betwmentioning
confidence: 99%
“…Cognitive disorganisation, which includes social anxiety, is associated with neuroticism (a preoccupation with negative affect) more than any other personality trait from the five-factor model (Swamih et al, 2011). Schizotypal traits denoting social avoidance, that is negative schizotypy, are associated with lower extraversion and agreeableness (Kwapil et al, 2008;Swamih et al 2011). Neuroticism could relate to RS (Berenson et al, 2009), but also mediate the link between negative schizotypy and RS by increasing early attention to rejection scenes, as defined by the P300 eventrelated potential (Premkumar et al, 2015).…”
Section: Social Quality Of Life (Qol) Could Explain the Relation Betwmentioning
confidence: 99%